Lignin oxidation by MnO2 under the irradiation of blue light. Issue 8 (19th March 2019) - Dai, Jinhuo; Patti, Antonio F.; Styles, Gavin N.; Nanayakkara, Sepa; Spiccia, Leone; Arena, Francesco; Italiano, Cristina; Saito, Kei
Abstract : We investigated a photocatalytic heterogeneous system using recyclable MnO2 under the irradiation of blue light for lignin oxidation. Abstract : Traditionally, conventional heat has been required for a large proportion of the oxidation and degradation process to utilise lignin from biomass. A photocatalysis system which is considered as a novel and green strategy for chemical reactions has been applied and a photo-MnO2 catalytic lignin oxidation method has been developed. In this study, we investigated a promising photocatalytic heterogeneous system for lignin oxidation. Recyclable MnO2 which is readily available and blue light which is a hazardless light are used in this system. 1-Phenylethanol was used as a model compound to study the suitable conditions for this system. After optimizing the reaction conditions, organosolv lignin, kraft lignin, and alkali lignin were applied to this system and the successful oxidation of lignins and their further degradation were shown.